The siege of Macindaw / 6. - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2009)
Will, who has become a protector of his first fief after many years as a Ranger's apprentice, is faced with many challenges when Keren, a renegade knight, takes over Castle Macindaw and forges a secret alliance with Scotti.